Gender, age, and sport differences in relative age effects among US Masters swimming and track and field athletes - Medic, N.; Young, B. W.; Starkes, J. L.; Weir, P. L.; Grove, J. R. (Journal of Sports Sciences, 2009)
A relative age effect has been identified in Masters sports (Medic, Starkes, & Young, 2007). Since gender, age, and type of sport have been found to influence the relative age effect in youth sports (Musch & Grondin, 2001), we examined how these three variables influenced possible relative age effects among Masters swimmers and track and field athletes. Using archived data between 1996 and 2006, frequency of participation entries and record-setting performances at the US Masters championships were examined as a function of an individual's constituent year within any 5-year age category. Study 1 investigated the frequency of Master athletes who participated; Study 2 examined the frequency of performance records that were set across constituent years within an age category, while accounting for the distribution of participation frequencies. Results showed that a participation-related relative age effect in Masters sports is stronger for males, that it becomes progressively stronger with each successive decade of life, and that it does not differ across track and field and swimming. In addition, a performance-related relative age effect in Masters sport seems to be stronger for swimming than track and field, but it does not differ across gender and decades of life.